Hospital Surge Capacity during Expo 2015 in Milano, Italy. Issue 5 (29th August 2018) - Faccincani, Roberto; Della Corte, Francesco; Sesana, Giovanni; Stucchi, Riccardo; Weinstein, Eric; Ashkenazi, Itamar; Ingrassia, Pierluigi
Abstract: Introduction: Hospital Acute Care Surge Capacity (HACSC), Hospital Acute Care Surge Threshold (HACST), and Total Hospital Capacity (THC) are scales that were developed to quantify surge capacity in the event of a multiple-casualty incident (MCI). These scales take into consideration the need for adequate care for both critical (T1) and moderate (T2) trauma patients. The objective of this study was to verify the validity of these scales in nine hospitals of the Milano (Italy) metropolitan area that prepared for a possible MCI during EXPO 2015. Methods: Both HACSC and HACST were computed for individual hospitals. These were compared to surge capacities declared by individual hospitals during EXPO 2015, and also to surge capacity evaluated during a simulation organized on August 23, 2016. Results: Both HACSC and HACST were smaller compared to capacities measured and reported by the hospitals, as well as those found during the simulation. This resulted in significant differences in THC when this was computed from the different methods of calculation. Conclusions: Surge capacity is dependent on the method of measurement. Each method has its inherent deficiencies. Until more reliable methodologies are developed, there is a benefit to analyze surge capacity using several methods rather than just one. Emergency committee members should be aware of the importance of critical resources when looking to the hospital capacity to respond to an MCI, and to the possibility to effectively increase it with a good preparedness plan. Since hospital capacity during real events is not static but dynamic, largely depending on occupation of the available resources, it is important that the regional command center and the hospitals receiving casualties constantly communicate on specific agreed upon critical resources, in order for the regional command center to timely evaluate the overall regional capacity and guarantee the appropriate distribution of the patients. R Faccincani, F Della Corte, G Sesana, R Stucchi, E Weinstein, I Ashkenazi, P Ingrassia .Hospital surge capacity during Expo 2015 in Milano, Italy .Prehosp Disaster Med .2018 ;33 (5 ):459 –465 .